Surgeon Performed Ultrasound in Assessing Thyroid Nodule Using American College of Radiology Tirads and Total Malignancy Score (TMS): A Validation Cross Sectional Study - Muhammed, Adi Syazni; Singh, Randeep; Abdullah Suhaimi, Shahrun Niza; Muhammad Latar, Nani Harlina (IIUM Medical Journal Malaysia, 2021)
INTRODUCTION: This study aims to evaluate the diagnostic reliability of the American College of Radiology Thyroid Imaging Report and Data System (ACR-TIRADS) and Total Malignancy Score (TMS) scoring system, in differentiating benign and malignant thyroid nodules. MATERIALS AND METHODS: This is a cross-sectional study involving patients with thyroid nodules treated at Hospital Canselor Tuanku Muhriz from October 2017 until October 2019. Ultrasound findings were scored according to the ACR[1]TIRADS and TMS scoring system. They were then correlated with the FNAC or histopathology report. The sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV) and diagnostic accuracy of both scoring system were calculated for analysis. RESULTS: A total of 150 patients with 223 thyroid nodules were included. 17% or 38 nodules were found to be malignant. The sensitivity, specificity, PPV, NPV and accuracy of ACR-TIRADS and TMS were 97.37% vs. 84.21 % , 52.97% vs. 62.70%, 29.84% vs. 31.68%, 98.99% vs. 95.08% and 61% vs. 66% respectively. According to the ACR-TIRADS, only hypoechoic nodules was a strong predictor of malignancy. Comparatively, in the TMS, strong predictors of malignancy include single nodule, hypoechogenicity, irregular margin, and nodules with peri and intranodular vascularity. CONCLUSION: Both ACR-TIRADS and TMS score had good diagnostic accuracy in predicting malignant thyroid nodule. TMS is comparable and not inferior to ACR[1]TIRADS however, the latter is more practical for use as growth and Doppler characteristic are not included in the assessment.